New insights into retinal circuits through EM connectomics: what we have learnt and what remains to be learned - Sawant, Abhilash; Saha, Aindrila; Khoussine, Jacob; Sinha, Raunak; Hoon, Mrinalini (Frontiers in Ophthalmology, 2023)
The retinal neural circuit is intricately wired for efficient processing of visual signals. This is well-supported by the specialized connections between retinal neurons at both the functional and ultrastructural levels. Through 3D electron microscopic (EM) reconstructions of retinal neurons and circuits we have learnt much about the specificities of connections within the retinal layers including new insights into how retinal neurons establish connections and perform sophisticated visual computations. This mini-review will summarize the retinal circuitry and provide details about the novel insights EM connectomics has brought into our understanding of the retinal circuitry. We will also discuss unresolved questions about the retinal circuitry that can be addressed by EM connectomics in the future.